Active Women over 50. Promoting Physical Activity in Women Over 50: A Randomized Trial. Issue 2 (February 2022) - Wallbank, Geraldine; Sherrington, Catherine; Hassett, Leanne; Canning, Colleen G.; Shepherd, Roberta; Richards, Bethan; Mackay, Catherine; Tiedemann, Anne
Purpose: This study aims to test the effect of an information and support intervention on physical activity (PA) in women aged 50+ years. Design: Randomized wait-list controlled trial. Setting: Sydney, Australia. Sample: 126 female university and health service employees, aged 50+. Intervention: Information session, activity tracker, regular motivational emails. Measures: Proportion achieving ≥ 10, 000 steps/day (primary outcome), daily step count, proportion meeting 150 mins/week of moderate to vigorous PA (MVPA), self-reported PA. Analysis: Odds-ratios and general linear regression models. Results: At 3 months, the intervention group reported significantly more vigorous PA (1.04 hours, 95% CI 0.24 to 1.85, P = .01, measured by IPAQ ), were more likely to achieve 300 mins/week of MVPA (OR = 1.98, 95% CI 0.89 to 4.36, P = .09, measured by Actigraph ) than the control wait-list group, and reported adopting PA promotion strategies (technology = 31/58% or goal-setting = 39/74%). No significant between-group differences in the primary outcome were detected (1.39, 95% CI 0.61 to 3.18, P = .44). Conclusions: This low-dose intervention significantly increased self-reported vigorous PA time and non-significantly increased the proportion of people achieving 300 mins/week of MVPA but did not significantly increase the proportion of participants achieving 10, 000 steps/day. Relatively small effects may be important at a population level given the minimal resources needed to deliver this intervention.